Candon master conservation plan a framework on how to manage local heritage resources - Lozano, Ludivina A.
The City of Candon in Ilocos Sur is rich in cultural built heritage, particularly of ancestral houses. There are ancestral houses identified by the city while other buildings and structures are not included in the list but can already be considered part of the cultural built heritage. Collectively, these cultural resources can be grouped within a proposed heritage district of the city, including a heritage growth corridor -- where the high concentration of such resources is located -- that may serve as visual representation and act as a living museum of the area. In this study, a proposed Master Conservation Plan was formulated, with the aim of preserving and protecting the identified built heritage resources in Candon City. A field survey was conducted to identify and map the local heritage resources and their cultural significance. After mapping the said resources, the boundaries of buffer zones were determined. Upon identification of the heritage district of the city, several guidelines regarding further development in the area, most especially along the heritage corridor, were recommended to preserve and protect these cultural resources from possible deterioration and/or destruction. Key words: conservation plan, cultural tourism, heritage zone, built heritage.